Exploring opportunities to integrate climate change into Gross National Happiness for Bhutan and its application for global wellbeing-centred Climate Resilient Development - Tashi Dorji; Angus Morrison-Saunders; David Blake (Environmental Management, 2026)
Climate change poses an increasing threat to human wellbeing, but despite this intricate relationship, addressing climate change rarely mainstreams wellbeing objectives. This study explores opportunities to integrate climate change into Bhutan’s development philosophy of Gross National Happiness (GNH) and examines how this experience can inform a wellbeing-centred global application through Climate Resilient Development (CRD). Using a qualitative design combining semi-structured interviews with 41 policy influencers in Bhutan, document analysis, and literature synthesis, this study identifies two complementary points of integration. The first involves identifying and then embedding climate-wellbeing stressors into the 9 domains and 33 GNH indicators used in the nationwide survey that constructs the GNH index. The second focuses on identifying and integrating climate-wellbeing stressors into the GNH screening tool through the 23 determinants used in assessing policies. Building on Bhutan’s GNH and climate experience, this study identifies six global pathways to operationalise wellbeing-centred CRD through strengthening governance and leadership, embedding wellbeing metrics into climate policy instruments, advancing knowledge pluralism and participatory co-production, linking local resilience to global frameworks, mobilising finance for wellbeing-oriented climate action, and multi-level integration. This study positions GNH as a globally relevant guide for transforming climate action towards human and planetary flourishing and offers an integrative approach for nations pursuing wellbeing objectives to combine these with climate action for holistic development. Its global relevance lies in offering a wellbeing-centred approach to CRD.

Navigating climate change in carbon negative Bhutan: Insights from policy influencers and comparison to the wider Himalayan region - Tashi Dorji; Angus Morrison-Saunders; David Blake (Journal of Mountain Science, 2026)
Climate change is one of the most pressing global challenges and spares no nation. Bhutan, as the only carbon negative country in the world, is no exception and being in the Himalayas – a region warming faster than the global average – further intensifies climate risks. This study explores how Bhutan navigates climate change through the perspectives of 41 policy influencers, including politicians, civil servants, and leaders from nongovernment organisations and the media. The findings are compared with scientific literature from the broader Himalayan region to identify shared vulnerabilities (e.g., glacial lake outburst floods, water scarcity, and agricultural disruptions) and governance challenges (e.g., financial constraints, geopolitical pressures, and gaps in policy implementation). The study reveals that Bhutan, like its Himalayan neighbours, prioritizes adaptation over mitigation due to immediate climate threats, despite its carbon-negative status. However, Bhutan faces unique pressures in upholding its dual commitments—maintaining 60% forest cover and carbon neutrality—amid competing development needs. While its Gross National Happiness (GNH) framework provides a holistic governance model, the analysis uncovers systemic barriers, including limited financing, transboundary climate risks, and uneven policy execution, which mirror regional struggles. The paper contributes to climate governance discourse by highlighting the risks of symbolic environmental pledges without robust implementation mechanisms, particularly for vulnerable mountain nations. It calls for integrated policies that bridge mitigation and adaptation, stronger regional cooperation, and equitable climate financing. The findings are relevant for policymakers in the Himalayas and international stakeholders advocating context-specific, justice-oriented climate strategies.

A practical mobile measurement approach for urban climate data collection: Proposing a method to investigate the cooling effect of urban green areas in Joondalup, Western Australia - Saman Galalizadeh; Angus Morrison-Saunders; Richard Silberstein; David Blake; Pierre Horwitz (Urban Forestry & Urban Greening, 2025)

Understanding the role qualitative methods can play in next generation impact assessment - Heidi Walker; Alan Bond; A. John Sinclair; Alan P. Diduck; Jenny Pope; Francois Retief; Angus Morrison-Saunders (Environmental Impact Assessment Review, 2025)

Understanding How Indigenous Knowledge Contributes to Climate Change Adaptation and Resilience: A Systematic Literature Review - Tashi Dorji; Kinley Rinchen; Angus Morrison-Saunders; David Blake; Vicki Banham; Sonam Pelden (Environmental Management, 2024)
Climate change is one of the biggest challenges facing the world today threatening societies and the future of the planet. The impacts of climate change are more severe in poor and marginalised populations like Indigenous communities where people rely heavily on their Indigenous Knowledge (IK) to adapt to the changing environment. Climate change adaptation and resilience are critical for the survival of Indigenous communities under the threat of climate change. This systematic literature review seeks to understand how IK contributes to climate change adaptation and resilience. A total of 71 papers from Scopus were analysed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. It investigated three research questions: (i) How is IK understood in climate change studies? (ii) What kind of IK is used to address climate change and enhance adaptation and resilience? and finally, (iii) What could be done to maximise the use of IK towards enhancing climate adaptation and resilience? The study found that Indigenous people use IK to predict extreme climatic conditions, prepare for it, and live through it making use of Indigenous adaptation strategies in multiple manifestations. The solutions to maximise the benefits of IK promote two dominant themes requiring more research on IK and climate change with diverse focus areas and the need to bridge it with scientific knowledge. This review provides a starting point for such research that will draw upon IK to enhance climate adaptation and resilience towards meaningful sustainable development.

The cooling impact of urban greening: A systematic review of methodologies and data sources - Saman Galalizadeh; Angus Morrison-Saunders; Pierre Horwitz; Richard Silberstein; David Blake (Urban Forestry & Urban Greening, 2024)

Editorial: Contemporary marine science, its utility and influence on regulation and government policy - Piers Larcombe; Angus Morrison-Saunders; Peter V. Ridd (Frontiers in Marine Science, 2024)

Investigating communication of findings in Environmental Impact Assessment and developing a research agenda for improvement - Alan Bond; Francois Retief; Angus Morrison-Saunders; Jenny Pope; Reece C. Alberts; Claudine Roos; Dirk Cilliers (Environmental Impact Assessment Review, 2024)

Understanding the impact of environmental impact assessment research on policy and practice - Angus Morrison-Saunders; Annette Nykiel; Nicole Atkins (Environmental Impact Assessment Review, 2024)

Understanding stakeholder experiences with visual communication in environmental impact assessment - Ana Roque de Oliveira; Sofia Bento; Maria Partidário; Angus Morrison-Saunders (Environmental Impact Assessment Review, 2023)

Understanding How Community Wellbeing is Affected by Climate Change: Evidence From a Systematic Literature Review - Tashi Dorji; Angus Morrison-Saunders; Dave Blake (Environmental Management, 2023)

Understanding community perceptions of an urban stream before and after a discussion of revitalization possibilities using photo-elicitation - Simone Lima da Costa Preuss; Jaime Joaquim da Silva Pereira Cabral; Angus Morrison-Saunders; Mike Hughes; Ana Bárbara de Araújo Nunes (Environment, Development and Sustainability, 2021)

When is an Offset Not an Offset? A Framework of Necessary Conditions for Biodiversity Offsets - Jenny Pope; Angus Morrison-Saunders; Alan Bond; Francois Retief (Environmental Management, 2021)

Practitioner Perspectives on the Role of Science in Environmental Impact Assessment - Angus Morrison-Saunders; John Bailey (Environmental Management, 2003)

Exploring the EIA/Environmental Management Relationship - Angus Morrison-Saunders (Environmental Management, 1999)